El extrañamiento cultural en espacios migratorios La juventud andaluza ante el reto de la multiculturalidad - Francisco Checa Olmos; Ángeles Arjona Garrido; Juan Carlos Checa Olmos (El Colegio de la Frontera Norte, A.C., 2007)
In this article, the authors seek to defi ne the system of cultural elements that cause cultural shock between Andalusian youths and the immigrant population. The interpretation of foreign cultures serves as the basis for analysing the origin of the problem and offers scope for refl ection in the face of the need for a new perspective on ethnic communication. The results show that the perception of the other is based on negative stereotypes that prevent peaceful multicultural coexistence.